Development of Interrelated Voltage Regulation System for Coal Mines Energy Efficiency Improving - Nepsha Fedor; Belyaevsky Roman (E3S Web of Conferences, 2018)
In this paper, the authors propose an algorithm for interrelated voltage regulation in the power supply system of coal mine which allows to provide a normative voltage level and to minimize the level of active power consumption. A feature of the proposed algorithm is a separate consideration of discrete and nondiscrete variables. Nondiscrete variables are represented as a state matrix. The optimization of nondiscrete variables is performed for each state. The algorithm chooses a state with the minimal active power consumption. The obtained values of discrete and nondiscrete variables are transferred in the form of control signals to voltage regulation devices. In this case, the periodicity of the switching is determined by the resource of the on-load tap-changing device. The use of this algorithm will theoretically allow increasing the energy efficiency of power supply systems of coal mines.